Essentials of Epidemiology in Public Health - Aschengrau, A. (MA, USA Jones & Bartlett Learning Inc., 2020)
Essentials of epidemiology in Public Health, Fourth Edition combines theory and practice in presenting traditional and new epidemiologic concepts and data sources.
Keywords: Seage G. R III; Epidemiology -- Public Health